Analisis Analisis Kemampuan Penalaran Adaptif dalam Memecahkan Masalah Matematika Ditinjau dari Tipe Kepribadian Siswa - Nada, Lisa Katun; Sridana, Nyoman; Wulandari, Nourma Pramestie; Hayati, Laila (Mandalika Mathematics and Educations Journal, 2024)
This study aims to describe the adaptive reasoning skill of students in solving mathematical problems based on the artisan, idealists, guardian and rational personality types. This research uses a qualitative approach with descriptive research type. The subjects of this research were 29 students in class VIIID of SMP Negeri 2 Labuapi for the 2024/2025 academic year. The interview subjects were 8 consistin, of 2 students with artisan personality type, 2 students with idealists personality type, 2 students with guardian personality type, and 2 students with rational personality type. The instruments used were personality type questionnaires, adaptive reasoning skill tests and interviews. The results of the analysis and discussion in this study indicate that students with artisan personality type have high adaptive reasoning skill, meeting five indicators of adaptive reasoning skill, namely making conjectures, providing reasons for answers, finding patterns, checking the truth of an argument, and drawing conclusions. Students with idealists’ personality type have high adaptive reasoning ability, meeting three indicators of adaptive reasoning skill, namely making conjectures, providing reasons for answers, and drawing conclusions. Students with guardian personality type have low adaptive reasoning skill and cannot meet the five indicators of adaptive reasoning skill. Students with rational personality type have moderate adaptive reasoning skill, meeting one indicator of adaptive reasoning skill, namely providing reasons for answers.